The Role Of The Teachers Gezag In The Learning Procses - Yola Anggraini Panjaitan; Feni Lanika (Proceeding International Seminar of Islamic Studies, 2019)
This study entitled the role of teacher gezag in the learning process. The problem that arises is the number of teachers who no longer have Gezaq (authority) and charism that is lost in the eyes of students so that several problems arise where the learning process cannot run properly. Moreover students in the learning process do not have a good relationship with the teacher so that the Gezag (authority) of the teacher is considered not good and is underestimated by them. The purpose of the research process is to find out how much influence the Gezag (authority) of a teacher to students in order to create a better learning process and teachers can be respected by students. The method used is library research, qualitative. Gezag (authority) of a teacher is very important in the learning process, because the teacher has a very important role in the learning process, where the authority of the teacher carries an influence on the learning process.